Is Ontological Modality Distinct from Logical Modality? Tracing the Dispute on Wujub, Imkan and Imtinaʿ in Kalam from Adud al-Din al-Iji to ʿAli Qushji - Ömer Türker (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
In his al-Mawāqif fī ʿilm al-kalām, ʿAḍud al-Dīn al-Ījī argues that the concepts of wujūb (necessity), imkān (possibility), and imtināʿ (impossibility) as analyzed in the general ontology (al-umūr al-ʿāmma) sections of later books are not the same as the wujūb, imkān, and imtināʿ of modal logic. The subsequent commentary tradition is almost unanimous in its criticism of Ījī on this point. Commentators of the Mawāqif such as Sayf al-Dīn al-Abharī, al-Sayyid al-Sharīf al-Jurjānī, and Ḥasan Çelebi; major commentators of the Tajrīd tradition; and the author of Sharḥ al-Maqāṣid, Saʿd al-Dīn al-Taftāzānī, all criticize Ījī’s claim. ʿAlī Qūshjī represents an important culmination of this series of criticism, with his notable synthesis of the critiques of Jurjāni and Taftāzānī. This paper firstly charts the trajectory of these critiques, by presenting and analyzing them in chronological order. Secondly, it makes the case that these critiques, though formally valid, in fact miss the mark, as they fail to recognize the full significance of the distinctions between existence and essence, and between wujūb and imkān. More specifically, the later scholars had not expressly renewed the definition of the concept of thubūt. Owing in large part to Ibn Sīnā’s distinctions between existence–essence and wājib–mumkin, thubūt in the later period radically diverged from the concept of existence, and in fact, the later scholars were using thubūt with this newer understanding in mind, despite this not always being made explicit. For this reason, it is more accurate to understand Ījī’s statement not as a mistaken point or a stating of the obvious; rather it is an expression of his understanding that a new era of metaphysical analysis had commenced, as well as a characterisation of the nature of this era.